A STUDY OF REFUSALS OF OFFERING ASSISTANCE IN ENGLISH AND VIETNAMESE - Ph.D. Trần Quang Hải (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
1. Investigate the specific conversations of giving refusals to an offer of assistance in English and Vietnamese languages. 2. Study the expressions that English and Vietnamese speakers use to refuse an offer of assistance and find out the culturally embedded factors that govern the choice of linguistic forms of refusing an offer of assistance